Preparation method of nano silicon-based negative electrode with double-layer structure and sulfide all-solid-state battery
By using a two-layer structure nano-silicon-based anode preparation method in sulfide all-solid lithium-ion batteries, the problems of low electronic conductivity and poor cyclic stability of pure silicon anode are solved, and higher specific capacity and cyclic stability are achieved. It also reduces costs and is suitable for large-scale applications of sulfide all-solid state batteries.
Patent Information
- Application Number
- CN202411315136.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-20
AI Technical Summary
In sulfide all-solid lithium-ion batteries, the electronic conductivity of pure silicon negative electrodes is low, the volume changes in circulation process are large, and the capacity retention rate is poor, resulting in short circuits easily when applied to the electrolyte membrane system and is relatively expensive.
Using the preparation method of a double-layer structure nano-silicon-based negative electrode, lithium silicon alloy is prepared by melting nano-silicon powder and metal lithium at a certain proportion of high temperature, and mixed with the binder to cover the current collector to form a double-layer structure, which is significantly Enhance electron transport at the interface between the negative electrode and the current collector and ion transport at the interface between the negative electrode and the electrolyte.
It significantly improves the electronic conductivity, cycle stability and specific capacity of the negative electrode, reduces costs, and is suitable for the large-scale and practical application of sulfide all-solid-state batteries.
Smart Images

Figure CN119170750A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a method for preparing a double-layer nano-silicon-based negative electrode and a sulfide all-solid-state battery. Background Art
[0002] As a lithium-ion battery, all-solid-state lithium-ion battery (ASSB) uses solid electrolyte instead of organic electrolyte. It has multiple advantages such as high safety, high energy density and low cost, and is expected to be used in future electric vehicles and large-scale energy storage. However, compared with the positive electrode, there are more uncertainties in the negative electrode of solid-state batteries. Intercalation type (such as graphite), high-energy alloy type materials (such as Si) and lithium metal negative electrodes are the main representative negative electrode materials of ASSB. Among them, Si has a theoretical specific capacity of up to 3590mAh g at room temperature. -1 , 10 times higher than graphite anode, close to the theoretical specific capacity of lithium metal, and with low risk of lithium dendrite growth, it is a very promising anode material. However, its poor initial Coulomb efficiency, large volume change during the cycle (>300%), low ion / electronic conductivity and fast capacity decay need to be solved urgently. Summary of the invention
[0003] The main purpose of the present invention is to provide a method for preparing a double-layer structured nano-silicon-based negative electrode and its application route in sulfide all-solid-state batteries, aiming to ensure that the content of active materials in the negative electrode is maximized while solving the problems of poor electronic conductivity, large volume change during the cycle process and rapid capacity decay of the existing pure silicon negative electrode, and to provide a route for the large-scale and practical application of sulfide all-solid-state soft-pack batteries.
[0004] To achieve the above object, the present invention provides a method for preparing a double-layer structured nano-silicon-based negative electrode, comprising the following steps:
[0005] (1) melting nano-sized silicon powder and metallic lithium at a certain ratio at high temperature to prepare a lithium silicon alloy, wherein the H2O and O2 contents in the preparation process are required to be less than 1 ppm, the melting temperature is 200 to 350° C., and the melting time is 1 to 6 hours;
[0006] (2) mixing the prepared lithium silicon alloy with a binder and coating the mixture on a current collector;
[0007] (3) Mixing nano-sized silicon powder with a binder and covering it on the coated lithium silicon alloy surface to obtain a double-layer structured nano-silicon-based negative electrode.
[0008] Preferably, the nano-sized silicon powder in steps (1) and (3) is nano-sized by ball milling twice, the time of the two ball millings is 1 to 8 hours, the ball milling speed is 400 to 800 rpm, and the ball milling medium is one or two of deionized water, ethanol, ethylene glycol, isopropanol, acetone, and n-butanol; the ratio of zirconium oxide ball milling beads in the first ball milling process is (5 to 10 mm): (2 to 4 mm) = (2 to 5): 1, and the ball-to-material ratio is (10 to 5): 1; the ratio of zirconium oxide ball milling beads in the second ball milling process is (5 to 10 mm): (2 to 4 mm): (0.4 to 1 mm) = 1: (2 to 5): (5 to 2), and the ball-to-material ratio is (40 to 20): 1.
[0009] Preferably, the ratio of nano-sized silicon powder to metallic lithium in step (1) is: based on the stoichiometric ratio, lithium is in excess of 10 wt%, wherein the stoichiometric ratio includes Li 1.71 Si, Li 2.25 Si, Li 2.33 Si, Li 3.75 Si, Li 4.4 One or more of Si.
[0010] Preferably, the high temperature melting in step (1) is to place the nanosized silicon powder and metallic lithium in a closed container and melt them in a high temperature melting device, wherein the high temperature melting device used includes one or more of a box furnace, a tube furnace, and a muffle furnace; and the closed container includes one or more of an iron crucible, a quartz crucible, and a tantalum crucible.
[0011] Preferably, the coating process in step (2) is to coat the lithium silicon alloy on the current collector by a wet coating process or a direct spraying process. The spraying equipment includes a manual spraying equipment, a semi-automatic spraying equipment and a fully automatic spraying equipment. The current collector material includes but is not limited to copper, nickel, titanium and iron.
[0012] Preferably, the binder used in steps (2) and (3) includes one or more of PTFE, PIB, BR, NBR, SEBS, SBR, PVDF, PIB, SBS, SR, HNBR, PEVA, PMMA and PAA, and the non-polar solvent used in the binder includes one or more of isopentane, n-pentane, cyclohexane, isooctane, cyclopentane, n-hexane, n-heptane, tetrahydrofuran, toluene, xylene, ethyl acetate, isobutyl isobutyrate, dichloromethane and chloroform.
[0013] Preferably, in step (2), the mass ratio of lithium silicon alloy to binder is (99-94):(1-6).
[0014] Preferably, the covering method in step (3) includes one or more of a dry process, a wet process, and a spray process; the dry process does not require drying; the wet process and the spray process require a drying temperature of 80 to 120° C. and a drying time of 8 to 24 hours.
[0015] Preferably, the mass ratio of silicon powder to lithium silicon alloy in step (3) is (50-90):(10-50).
[0016] The present invention also provides a sulfide all-solid-state battery, comprising a double-layer structured nano-silicon-based negative electrode, an electrolyte membrane and a dry-process positive electrode prepared by any of the above methods.
[0017] The positive electrode includes one or more of NCM111, NCM424, NCM523, NCM622, or NCM811.
[0018] Among them, the electrolyte includes Li2S-P2S5, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl, Li 10 SnP2S 12 , or Li 10 GeP2S 12 One or more of .
[0019] The technical concept of the present invention is as follows:
[0020] Silicon anode has a high capacity of 3590 mAh g at room temperature. -1 Theoretical specific capacity is a promising sulfide solid-state battery negative electrode material. However, in the sulfide solid-state battery system, the pure silicon negative electrode system has low ion / electronic conductivity, large volume change during the cycle process, poor capacity retention, and is prone to short circuit when applied to the electrolyte membrane system.
[0021] In order to solve the problems of pure silicon negative electrode pulverization and low capacity retention, nano-silicon and metallic lithium were used as raw materials to prepare lithium-silicon alloy with advantages of both ion and electron conductivity, and a silicon-based negative electrode with a double-layer structure was designed. This double-layer structure enriches lithium-silicon alloy on the current collector side without losing the proportion of negative electrode active materials, significantly enhancing the electron transmission at the interface between the negative electrode and the current collector. At the same time, the lithium-silicon alloy with low Young's modulus alleviates the pulverization of silicon on Li +The transmission path is destroyed, thereby indirectly enhancing the ion transmission at the interface between the negative electrode and the electrolyte. The double-layer structure is applied to soft-pack batteries based on sulfide electrolyte membranes, which is suitable for practical and large-scale production.
[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0023] (1) The present invention uses nano-silicon and metallic lithium as raw materials and adopts a high-temperature melting method to obtain a lithium-silicon alloy, whose electronic conductivity is as high as 17.2 mScm -1 , much higher than the electronic conductivity of silicon (0.000611mScm -1 ).
[0024] (2) Compared with micron silicon, the atoms on the surface of nano silicon have a higher average binding energy, which can better release stress during the volume expansion of the silicon negative electrode and effectively avoid structural collapse. At the same time, the nanostructure shortens the Li + The diffusion distance of Li + Diffusion path. However, the cost of nano-silicon on the market is high. By using a simple ball milling process to nano-size silicon, the cost can be greatly reduced.
[0025] (3) Compared with pure silicon anode, the double-layer structured nano-silicon-based anode has higher specific capacity and cycle stability in all-solid-state lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM characterization image of the nanopowder obtained after ball milling in Example 1;
[0027] Figure 2 Li prepared in Example 1 4.4 SEM characterization of Si;
[0028] Figure 3 is the ionic / electronic conductivity of the lithium silicon alloy powder and the silicon powder in Example 1;
[0029] Figure 4 The XRD diagram of the double-layer nano-silicon-based negative electrode provided in Example 1;
[0030] Figure 5 This is a SEM characterization image of the double-layer structure nano-silicon-based negative electrode provided in Example 1;
[0031] Figure 6 It is a schematic diagram of the principle of a battery prepared by the double-layer structure nano silicon-based negative electrode of the present invention;
[0032] Figure 7 This is a structural diagram of a soft-pack battery prepared by a double-layer nano-silicon-based negative electrode of the present invention;
[0033] Figure 8 is a cycle stability diagram of a battery prepared by the double-layer structure nano-silicon-based negative electrode of Example 1;
[0034] Fig. 9 1 is a comparison chart of the cycle stability of batteries prepared by the double-layer structure nano-silicon-based negative electrodes of Examples 1 to 3;
[0035] Fig.10 This is the usage scenario of the soft-pack battery prepared by the double-layer structure nano-silicon-based negative electrode of the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention.
[0037] Embodiment 1:
[0038] Weigh 2g of micron silicon and put it into a zirconia ball mill. Use deionized water as a ball milling agent. First, use 18g of ball milling beads with a ratio of 5mm:2mm=5:1 for 2h, and then use 80g of ball milling beads with a ratio of 5mm:3mm:1mm=1:5:2 for 2h. The entire ball mill revolution speed is 800rpm. The ball milling beads are zirconia ball milling beads. Figure 1 As shown, the particle size of the powder after ball milling is hundreds of nanometers.
[0039] Nano-silicon powder and metallic lithium were weighed in a ratio of 1:4.4, with an excess of 10 wt% lithium, and melted at 300 °C for 1 h to obtain Li 4.4 Si. Figure 2 As shown, the particles shown by SEM are Li 4.4 Si, particle size is about 5-10μm. In addition, please refer to Figure 3 , Li at room temperature 4.4 The ionic conductivity of Si is about 0.61 mS cm -1 , the electronic conductivity is 17.20 mS cm -1 , which is much higher than the ionic conductivity and electronic conductivity of nSi at room temperature.
[0040] Weigh 400 mg of silicon powder and Li in a ratio of 40:10 4.4 Si 100 mg, weigh 42 mg mL -1 PVDF / isobutyl isobutyrate 400 μL and 100 μL of binder solution, first 4.4 Si is coated on copper foil, dried at 80℃ and then coated on Li 4.4 Si surface, a double-layer structure nano-silicon-based negative electrode is obtained. Figure 4 As shown, the diffraction peak at 40.98° is Li 4.4The characteristic peaks of Si. Figure 5 As shown, SEM cross section shows nSi and Li 4.4 Si obvious stratification.
[0041] Please refer to Figure 6 and Figure 7 The double-layer nano-silicon-based anode was assembled into a full battery with the structure of double-layer nano-silicon-based anode|Li6PS5Cl|NCM811, and compared with the full battery of pure silicon anode, its cycle performance was much better than that of pure silicon anode ( Figure 8 ).
[0042] Embodiment 2:
[0043] Weigh 2g of micron silicon, put it into a zirconia ball mill, use deionized water as the ball milling agent, first use 18g of ball milling beads with a ratio of 5mm:2mm=5:1 for 2h, and then use 80g of ball milling beads with a ratio of 5mm:3mm:1mm=1:5:2 for 2h. The entire ball mill has an orbital speed of 800rpm and the ball mill beads are zirconia ball milling beads.
[0044] Nano-silicon powder and metallic lithium were weighed in a ratio of 1:4.4, with an excess of 10 wt% lithium, and melted at 300 °C for 1 h to obtain Li 4.4 Four.
[0045] Weigh 600 mg of silicon powder and Li in a ratio of 60:10 4.4 Si 100 mg, weigh 42 mg mL -1 PVDF / isobutyl isobutyrate 600 μL and 100 μL of binder solution, first 4.4 Si is coated on copper foil, dried at 80℃ and then coated on Li 4.4 Si surface, and obtain a double-layer structure nano-silicon-based negative electrode.
[0046] The double-layer structured nano-silicon-based negative electrode is assembled into a full battery with the structure of double-layer structured nano-silicon-based negative electrode|Li6PS5Cl|NCM811.
[0047] Embodiment three:
[0048] Weigh 2g of micron silicon, put it into a zirconia ball mill, use deionized water as the ball milling agent, first use 18g of ball milling beads with a ratio of 5mm:2mm=5:1 for 2h, and then use 80g of ball milling beads with a ratio of 5mm:3mm:1mm=1:5:2 for 2h. The entire ball mill has an orbital speed of 800rpm and the ball mill beads are zirconia ball milling beads.
[0049] Nano-silicon powder and metallic lithium were weighed in a ratio of 1:4.4, with an excess of 10 wt% lithium, and melted at 300 °C for 1 h to obtain Li 4.4 Four.
[0050] Weigh 200 mg of silicon powder and Li in a ratio of 20:10 4.4 Si 100 mg, weigh 42 mg mL -1 PVDF / isobutyl isobutyrate 200 μL and 100 μL of binder solution, first 4.4 Si is coated on copper foil, dried at 80℃ and then coated on Li 4.4 Si surface, and obtain a double-layer structure nano-silicon-based negative electrode.
[0051] The double-layer structured nano-silicon-based negative electrode is assembled into a full battery with the structure of double-layer structured nano-silicon-based negative electrode|Li6PS5Cl|NCM811.
[0052] Fig. 9 The figure shows the cycle stability comparison of the battery prepared by the double-layer structure nano silicon-based negative electrode of Example 1-3. 4.4 Si = 4:1 (mass ratio) was determined to be the optimal ratio for the double-layer fully active silicon-based anode (nSi-Li 4.4 Si-DL4). The negative electrode structure under this ratio has the best rate performance and cycle performance. 4.4 Si=6:1(nSi-Li 4.4 Si-DL6), nSi:Li in Example 3 4.4 Si=2:1(nSi-Li 4.4 Si-DL2).
Claims
1. A method for preparing a double-layer structured nano-silicon-based negative electrode, characterized in that: The method comprises the following steps: (1) melting nano-sized silicon powder and metallic lithium at a certain ratio at high temperature to prepare a lithium silicon alloy, wherein the H2O and O2 contents in the preparation process are required to be less than 1 ppm, the melting temperature is 200 to 350° C., and the melting time is 1 to 6 hours; (2) mixing the prepared lithium silicon alloy with a binder and coating the mixture on a current collector; (3) Mixing nano-sized silicon powder with a binder and covering it on the coated lithium silicon alloy surface to obtain a double-layer structured nano-silicon-based negative electrode.
2. The preparation method according to claim 1, characterized in that: The nano-sized silicon powder in steps (1) and (3) is nano-sized by ball milling twice, the time of the two ball millings is 1 to 8 hours, the ball milling speed is 400 to 800 rpm, and the ball milling medium is one or two of deionized water, ethanol, ethylene glycol, isopropanol, acetone, and n-butanol; the ratio of zirconium oxide ball milling beads in the first ball milling process is (5 to 10 mm): (2 to 4 mm) = (2 to 5): 1, and the ball-to-material ratio is (10 to 5): 1; the ratio of zirconium oxide ball milling beads in the second ball milling process is (5 to 10 mm): (2 to 4 mm): (0.4 to 1 mm) = 1: (2 to 5): (5 to 2), and the ball-to-material ratio is (40 to 20):
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the ratio of nano-sized silicon powder to metallic lithium is: based on the stoichiometric ratio, lithium is in excess of 10 wt%, wherein the stoichiometric ratio includes Li 1.71 Si、Li 2.25 Si、Li 2.33 Si、Li 3.75 Si、Li 4.4 Si one or more.
4. The preparation method according to claim 1, characterized in that: The high temperature melting in step (1) is to place the nanosized silicon powder and metallic lithium in a closed container and melt them in a high temperature melting device, wherein the high temperature melting device used includes one or more of a box furnace, a tube furnace, and a muffle furnace; and the closed container includes one or more of an iron crucible, a quartz crucible, and a tantalum crucible.
5. The preparation method according to claim 1, characterized in that: The coating process in step (2) is to coat the lithium silicon alloy on the current collector by a wet coating process or a direct spraying process.
6. The preparation method according to claim 1, characterized in that: The binder used in the steps (2) and (3) includes one or more of PTFE, PIB, BR, NBR, SEBS, SBR, PVDF, PIB, SBS, SR, HNBR, PEVA, PMMA and PAA, and the non-polar solvent used in the binder includes one or more of isopentane, n-pentane, cyclohexane, isooctane, cyclopentane, n-hexane, n-heptane, tetrahydrofuran, toluene, xylene, ethyl acetate, isobutyl isobutyrate, dichloromethane and chloroform.
7. The preparation method according to claim 1, characterized in that: The mass ratio of lithium silicon alloy to binder in step (2) is (99-94):(1-6).
8. The preparation method according to claim 1, characterized in that: The covering method in step (3) includes one or more of a dry process, a wet process, and a spray process; the dry process does not require drying; the wet process and the spray process require a drying temperature of 80 to 120° C. and a drying time of 8 to 24 hours.
9. The preparation method according to claim 1, characterized in that: The mass ratio of silicon powder to lithium silicon alloy in step (3) is (50-90):(10-50).
10. A sulfide all-solid-state battery, characterized in that: A double-layer nano-silicon-based negative electrode prepared by the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium-silicon alloy negative electrode preparation method and sulfide all-solid-state battery
CN114744161A
3D double-layer lithium negative electrode, preparation method thereof and sulfide all-solid-state lithium ion battery containing 3D double-layer lithium negative electrode
CN114843526A
Composite silicon-based negative electrode material, negative electrode plate and all-solid-state lithium battery
CN115117331A
Composite silicon-based negative electrode material and preparation method thereof
CN118281205A
Negative electrode active material, preparation method thereof, negative electrode including the negative electrode active material, and secondary battery including the negative electrode
US20200388833A1
Cited By
Interface protection layer of lithium metal negative electrode as well as preparation method and application of interface protection layer
CN121123283A
